Gambaran Motif dan Beliefs pada Jamaah Asmaul Haq Rangkah Kidul Sidoarjo - Ranggi, Desta; Herani, Ika; Lestari, Sumi (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2015)
The aim of this study was overview about the motive and beliefs of individual who are member of the Asmaul Haq. The method called